TEKNIK PEMBUATAN ANTI VIRUS DENGAN METODE PENCARIAN DATA HEADER FILE MENGGUNAKAN VISUAL BASIC 6.0 - Purwanto, Hari (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2015)
Technological advances, especially in the field of information technology in the last decade has changed very quickly where the computer in a few decades ago, only used as a word processor and so on. A computer virus is a computer program that can duplicate or copy itself and spreads by inserting copies of itself into other programs or documents. Computer viruses can be destructive nature for example by destroying the data on the document, make computer users feel disturbed by their presence in a computer system, and does not cause deleterious effects at all. Antivirus is a type of software that is used to detect and remove computer viruses from the computer system. Antivirus Software Virus Protection is also called, because the application can determine whether a computer system has been infected with a virus or not. In this paper the author tries to raise the issue by making Antivirus. This application is built using Microsoft Visual Basic 6.0.